Leaders in the Classroom: Using Teaching as a Context for Measuring Leader Identity - Nadelson, Louis S.; Booher, Loi; Turley, Michael (Frontiers in Education, 2020)
We based our exploratory study on the premise that the role of a K-12 teacher in the classroom is that of a leader. Teachers must identify as leaders to effectively navigate the challenges of teaching and learning. In our research, we developed and validated a tool containing both quantitative and qualitative items to assess the attributes of the leader identity of teachers in the context of their role as a classroom teacher. The responses of the 91 K-12 teachers who participated in our research revealed variations in the levels of leader identity attributes based on individual differences. We found most teachers tended to perceive the primary role of a teacher as a conveyer of knowledge, and yet strongly agreed that teachers are critical role models. We also found a disconnect between why they became teachers and their perceptions of the role of a teacher. Following our results, we interpret our findings, provide associated implications, and offer directions for future research.